Benefit evaluation of the deep peak-regulation market in the northeast China grid - Hongyan Ma; Zheng Yan; Mingjie Li; Dong Han; Xiao Han; Yiqun Song; Ping Wei; Gang Li; Yongjun Liu (CSEE Journal of Power and Energy Systems, 2019)
In the Northeast China Grid (NCG), the percentage of wind power has reached nearly 20% of the total installed generation capacity, which causes increasing demands for deep peak-regulation capacity (DPC) during the operation of power systems. The shortage of DPC has become a significant problem in the NCG which may lead to wind curtailments and affect the security of power systems as well as the heating needs for inhabitants. In order to cope with this DPC shortage issue, the deep peak-regulation market (DPM) was established and has been running steadily in the past few years in NCG. This paper elaborates on the roles of the market players and the operational processes of the DPM, of which the advancements in terms of management mechanism are summarized. Moreover, benefits of the DPM for social harmony, environmental protection and economic efficiency are analyzed, for which relevant evaluation indices are proposed. A five-unit simulation system is constructed to illustrate the operation and benefits of the DPM. And focusing on comparisons with the previous Two Rules, the case study of Liaoning Power Grid verifies further that the DPM is feasible and able to bring more benefits to grids.